2011
DOI: 10.1177/0022022111405657
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Parental and Peer Support in Relation to Canadian, Cuban, and Spanish Adolescents’ Valuing of Academics and Intrinsic Academic Motivation

Abstract: The aim of this study was to explore possible parent and peer influences on adolescents’ valuing of academics and intrinsic academic motivation in cultures varying in traditional emphasis on the family unit (Cuba, Canada, and Spain). Perceived parent and peer support, parents’ expectations, and valuing of academics significantly predicted adolescents’ valuing of education and motivation. Spanish adolescents were less motivated than members of the other ethnic groups. The Spanish participants also reported lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Peers valuing of school and high educational aspirations help shape adolescents’ valuing of education and academic motivation (Nelson & DeBacker, 2008, Vitoroulis, Schneider, Vasquez, de Toro, & Gonzáles, 2012), contributing to positive academic identity, which is significantly associated with school success independent of other family and school-level contributors (Prince & Nurius, 2014). Factors such as positive school affiliation, a safe learning environment, and peer and family support are positively associated with adolescents’ sense of subjective health (Almgren, Magarati, & Mogford, 2009).…”
Section: Family Peer and School Assets To Buffer Effects Of Cumulatimentioning
confidence: 99%
“…Peers valuing of school and high educational aspirations help shape adolescents’ valuing of education and academic motivation (Nelson & DeBacker, 2008, Vitoroulis, Schneider, Vasquez, de Toro, & Gonzáles, 2012), contributing to positive academic identity, which is significantly associated with school success independent of other family and school-level contributors (Prince & Nurius, 2014). Factors such as positive school affiliation, a safe learning environment, and peer and family support are positively associated with adolescents’ sense of subjective health (Almgren, Magarati, & Mogford, 2009).…”
Section: Family Peer and School Assets To Buffer Effects Of Cumulatimentioning
confidence: 99%
“…In contrast, Canadian schools stress the development and maintenance of social skills, for example with peers and teachers, which consequently helps build a supportive scholastic environment ( Wilson and Lam, 2004 ). One particular cross-national study found that Canadian students especially value social support from friends at school, which was related to high levels of intrinsic achievement motivation ( Vitoroulis et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…While parental influence on adolescents' academic perceptions has been previously studied (i.e., Kirk, Lewis-Moss, Nilsen, & Colvin, 2011), limited research has explored the impact of parental documentation status on Latino adolescents' academic expectations and aspirations. Concomitantly, having an undocumented parent could possibly present several direct and indirect barriers to an adolescent's academic career because parents are often a large factor in students' academic career (Vitoroulis, Schneider, Vasquez, De Toro, & Gonzáles, 2012). More specifically, parental characteristics have been especially salient to the success of Latino adolescents (Dumka, Gonzales, Bonds, & Millsap, 2009) to which parental documentation issues may hinder.…”
Section: Latino Adolescents and Academic Outcomesmentioning
confidence: 99%